Nature and narratives; landscapes, plants and animals in Palaiologan vernacular literature - Stewart, K (2015)
This thesis identifies the role of nature within Palaiologan entertainment literature. The texts on which this thesis focuses include a selection of the Palaiologan novels, namely the Achilleid, Velthandros and Chrysandza, Kallimachos and Chrysorroi and Livistros and Rodamni, as well as two other, more satirical works, The Synaxarion of the Honourable Donkey, and An Entertaining Tale of Quadrupeds. These texts seem to be different from earlier works in which nature is prominent, utilising such material in an innovative way. The study of these texts provides us with information both on the Byzantine view of the natural world and on the use of literature during a particularly troubled period of Byzantine history. My main questions therefore are how nature is portrayed in these texts and what can this tell us about the society that produced them. The study of these vernacular texts indicates that the natural world is given a prominent place in the literature of the period, using landscapes, plants and animals in diverse ways to express assorted ideas, or to stress particular aspects of the stories. The animals and landscapes provide hints of the plot to the audience, which the authors sometimes then subvert. The authors draw on earlier Greek material, but parallels with literature from other cultures show similarities which imply a shared medieval perspective on nature with local differences.